Translating Linguistic Terms: A Case Study of French and Russian Terminologies - Denis S. Zolotukhin (Polylinguality and Transcultural Practices)
This paper explores the conceptual, semantic and formal features of linguistic terms that emerge in the process of selecting equivalents when translating scientific texts on linguistics from French to Russian and vice versa. Based on epistemological and terminological approaches, as well as existing translation practices in this field, a systematization of the linguistic term parameters is carried out. These parameters must be considered when translating both works of previous centuries and contemporary texts. By analyzing translation challenges, explicitly discussed in the commentary of published translations, the paper reveals the interrelations among terminological parameters in both synchronic and diachronic perspectives, at conceptual and linguistic levels. The analysis focuses on the translations of foundational texts by French- and Russian-speaking linguists (e.g., Potebnja, Saussure, Benveniste, Lotman), and on bilingual and monolingual dictionaries of linguistic terminology. The author identifies 36 French terminological units that warrant special attention from Russian-speaking translators, academic authors, and terminographers. Through contextual, definitional, and component analysis of the selected terminological units, this study reveals their lexical-semantic and morphological characteristics, as well as the specifics of their conceptual relationships. It proposes concrete solutions to recurring translation challenges and argues for a comprehensive approach that accounts for the language, conceptual, spatial, temporal, and epistemological dimensions of terminology. This approach is intended to improve translation accuracy, enhance the content of linguistic terminology dictionaries, and strengthen scientific communication between French- and Russian-speaking linguists.